GGC Repeat Expansion in the NOTCH2NLC Gene Is Associated With a Phenotype of Predominant Motor–Sensory and Autonomic Neuropathy - Wang, Hui; Yu, Jiaxi; Yu, Meng; Deng, Jianwen; Zhang, Wei; Lv, He; Liu, Jing; Shi, Xin; Liang, Wei; Jia, Zhirong; Hong, Daojun; Meng, Lingchao; et al. (Frontiers in Genetics, 2021)
There is still a considerable proportion of patients with inherited peripheral neuropathy (IPN) whose pathogenic genes are unknown. This study was intended to investigate whether the GGC repeat expansion in the NOTCH2NLC is presented in some patients with IPN. A total of 142 unrelated mainland Chinese patients with highly suspected diagnosis of IPN without any known causative gene were recruited. Repeat-primed polymerase chain reaction (RP-PCR) was performed to screen GGC repeat expansion in NOTCH2NLC, followed by fluorescence amplicon length analysis-PCR (AL-PCR) to determine the GGC repeat size. Detailed clinical data as well as nerve, muscle, and skin biopsy were reviewed and analyzed in the NOTCH2NLC-related IPN patients. In total, five of the 142 patients (3.52%) were found to have pathogenic GGC expansion in NOTCH2NLC, with repeat size ranging from 126 to 206 repeats. All the NOTCH2NLC-related IPN patients presented with adult-onset motor–sensory and autonomic neuropathy that predominantly affected the motor component of peripheral nerves. While tremor and irritating dry cough were noted in four-fifths of the patients, no other signs of the central nervous system were presented. Electrophysiological studies revealed both demyelinating and axonal changes of polyneuropathy that were more severe in lower limbs and asymmetrically in upper limbs. Sural nerve pathology was characterized by multiple fibers with thin myelination, indicating a predominant demyelinating process. Muscle pathology was consistent with neuropathic changes. P62-positive intranuclear inclusions were observed in nerve, skin, and muscle tissues. Our study has demonstrated that GGC expansion in NOTCH2NLC is associated with IPN presenting as predominant motor–sensory and autonomic neuropathy, which expands the phenotype of the NOTCH2NLC-related repeat expansion spectrum. Screening of GGC repeat expansions in the NOTCH2NLC should be considered in patients presenting with peripheral neuropathy with tremor and irritating dry cough.